A Beautiful Grave: Innocent Objects, Museums, and the Modern Self in Driss Chraïbi's La Civilisation, ma Mère!... and the Ben M'Sik Community Museum - Katarzyna Pieprzak (Studies in 20th & 21st Century Literature, 2014)
Two-thirds through Driss Chraïbi’s 1972 novel La Civilisation, ma Mère!... ‘Mother Comes of Age’ about an un-named Moroccan woman and her path to modernity, the Mother makes a powerful statement that innocent objects from her past deserve a beautiful tomb and preservation from ridicule. In this article, I discuss the idea of innocent objects – innocent in terms of unknowing, and innocent in juridical terms as absolved from guilt in a crime and undeserving of punishment – in relationship to the Mother’s tomb and the 2006 Casablanca Ben M’Sik Community Museum (BMCM). Both the novel and the museum house seemingly worthless objects – from combs to old teapots – that nonetheless testify to the creation of the modern self. In the case of the BMCM, a museum whose role is to document oral history in Casablanca’s formerly largest bidonville ‘shantytown,’ inhabitants have been stepping forward, uninvited, and bringing objects to the museum. Much like Chraïbi’s Mother, these inhabitants are eager to preserve the innocence of their past in the face of modernity – for them, a modern urbanism that is destroying their neighborhood to produce new public housing, and an on-going state discourse that has labeled them as dissidents, criminals and even terrorists.
Keywords: Museums; Driss Chraïbi; La Civilisation ma Mère; Mother Comes of Age; Ben M' Sik; Morocco; Innocent